2020
DOI: 10.1177/0960327120924080
|View full text |Cite
|
Sign up to set email alerts
|

MiR-655-3p inhibits the progression of osteoporosis by targeting LSD1 and activating BMP-2/Smad signaling pathway

Abstract: Osteoporosis (OP) is one of the most common chronic metabolic bone diseases in the seniors and postmenopausal women. Plenty of microRNAs (miRNAs) have been confirmed to be involved in OP progression. However, the role of miR-655-3p in osteogenic differentiation and bone formation was still unclear. In this study, we aimed to investigate the cellular function of miR-655-3p and its underlying mechanism in OP. We found that miR-655-3p expression was downregulated in both ovariectomized (OVX) mice bone tissues and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In addition, our results elicited that LSD1 expression was decreased in hPDLSCs undergoing osteogenic induction. Consistently, a pioneering research elucidated that LSD1 exhaustion facilitated bone formation and MSC osteogenic differentiation and sabotaged cell death (Wang, Liu, et al, 2020). Next, to elaborately explore the role of LSD1 in periodontitis, hPDLSCs were transduced with si‐LSD1 to reduce LSD1 expression, and the results supported that LSD1 knockdown accelerated osteogenic differentiation of hPDLSCs in inflammatory microenvironment as presented by the promoted levels of Runx2, OCN, and ALP.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, our results elicited that LSD1 expression was decreased in hPDLSCs undergoing osteogenic induction. Consistently, a pioneering research elucidated that LSD1 exhaustion facilitated bone formation and MSC osteogenic differentiation and sabotaged cell death (Wang, Liu, et al, 2020). Next, to elaborately explore the role of LSD1 in periodontitis, hPDLSCs were transduced with si‐LSD1 to reduce LSD1 expression, and the results supported that LSD1 knockdown accelerated osteogenic differentiation of hPDLSCs in inflammatory microenvironment as presented by the promoted levels of Runx2, OCN, and ALP.…”
Section: Discussionmentioning
confidence: 86%
“…Inhibition of miR-655-3p by NFIA-AS2 remarkably conduced to cell proliferation, motility, and impeded apoptosis in glioma via enhancing the expression of ZFX (Xin et al, 2020). Through targeting LSD1 to activate BMP-2/Smad pathway, miR-655-3p hindered the progression of osteoporosis (Wang et al, 2020b). In our research, we probed the function of exosomecarried miR-655-3p by transfecting miR-655-3p mimics or inhibitor into PTC cells.…”
Section: Discussionmentioning
confidence: 95%
“…It has been demonstrated that lysine-specific histone demethylase 1 (LSD1) is the downstream target gene of miR-655-3p, which further effected the BMP-2/Smad signaling to promote osteogenesis. 68 Caspase-3 is one of the most critical components in the activation of the apoptosis cascade. Therefore, downregulation of caspase-3 can block the process of apoptosis.…”
Section: Mirnas In Regulating Osteoblast Apoptosismentioning
confidence: 99%